(3GdfXQjI GdGbJUGOjI (B:s (3JMdjd LRFj hcdj ddeHGOF (B/s - (3YHO GdMejO, YHO GdeWdHs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3eaGgje CSGSjI Mhd GdfXQjI GdGbJUGOjI hGdfXe GdGbJUGOjI,GdfXQjI GdGbJUGOjI GdLRFjI(B((3eHGOF GdJMdjd GdLRFj(B)(3,GdfXQjI GdGbJUGOjI GdcdjI(B((3eHGOF GdJMdjd Gdcdj(B)s
(3HHdjhZQGajG(B:(3U(B.7-10s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdLRFjs; (3GdGbJUGO Gdcdjs